ANTISEMITISM AND ANTIZIONISM IN THE HISTORICAL AND CONTEMPORARY BRAZILIAN PERSPECTIVE (CIPEEX, 2025)
This work explores the complexity of antisemitism through a multidimensional analysis, focusing on its historical and contemporary manifestation, as well as strategies for its combat. Using a methodology based on bibliographical research, the study deepens in works of renowned authors such as Adorno, Butler, and Carneiro, among others, to unravel the roots of anti-Semitism and its intersections with phenomena such as nationalism, authoritarianism and racism. The work reveals that anti-Semitism transcends specific periods and contexts, being shaped and influenced by various social, political and economic forces. The results highlight the importance of education, especially in the digital sphere, as a vital tool in the fight against anti-Semitism, promoting critical thinking, empathy and awareness about the intersectionality of oppressions. It is concluded that the fight against anti-Semitism requires a continuous collective effort, which involves the preservation of historical memory, the promotion of inclusive narratives and active engagement against all forms of prejudice and discrimination.
Keywords: anti-semitism; anti-zionism; digital education